KEBIJAKAN PRESIDEN DONALD TRUMP MENGAKUI YERUSALEM MENJADI IBU KOTA ISRAEL - Sibarani, Jovita Paulina; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
In 2017, President Donald Trump officially recognized Jerusalem as the capital of Israel and relocated the United States Embassy from Tel Aviv to Jerusalem, marking a major turning point in the direction of U.S. foreign policy regarding the Israeli-Palestinian conflict. This research focuses on analyzing the underlying factors behind this decision, with particular attention to the influence of major lobbying groups such as AIPAC and Evangelical Christian groups in the formulation of U.S. foreign policy. The findings of this research indicate that domestic political motivations and the interests of lobbying groups played a significant role in the decision to recognize Jerusalem, which not only affected U.S - Israeli relations but also sparked international reactions regarding prospects for peace in the Middle East. The conclusion of this study asserts that U.S. foreign policy in this case was driven more by domestic political calculations and pressure from interest groups than by consideration of international law. Keywords: United States Foreign Policy, AIPAC, Evangelical Christian Groups, Political Lobbying Groups, Israeli-Palestinian Conflict.